96=6(f+4)

Simple and best practice solution for 96=6(f+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 96=6(f+4) equation:


Simplifying
96 = 6(f + 4)

Reorder the terms:
96 = 6(4 + f)
96 = (4 * 6 + f * 6)
96 = (24 + 6f)

Solving
96 = 24 + 6f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-6f' to each side of the equation.
96 + -6f = 24 + 6f + -6f

Combine like terms: 6f + -6f = 0
96 + -6f = 24 + 0
96 + -6f = 24

Add '-96' to each side of the equation.
96 + -96 + -6f = 24 + -96

Combine like terms: 96 + -96 = 0
0 + -6f = 24 + -96
-6f = 24 + -96

Combine like terms: 24 + -96 = -72
-6f = -72

Divide each side by '-6'.
f = 12

Simplifying
f = 12

See similar equations:

| 17=n+2-4n | | 90=9(d+4) | | y=7x+134 | | 3(g+3)+2=20 | | y=7x+135 | | 2x-4=2(x+1)+2 | | 3(q-6)-2=4 | | 7(-2y+2)-3y=71 | | 5f+18=11f | | 9-z=-10 | | 11-h=17 | | rs/24-d=t | | -2(b+15)+9=-11 | | 2(4s+10)=52 | | 22.36+4.73=64.93 | | F(x)=x^3-1.5x^2+1.75 | | 47-y=183 | | 7(2l+10)=40 | | -5(x+4)=-(5x+20) | | -(c+5)=2 | | -3.5=-3y-7.1 | | 9v/15=0*15 | | 1/12n=11 | | 10m+3=23 | | 3sin(x)+sqrt(7)*cos(x)=2 | | 5m+9n=15form | | 4=2(d-6) | | 8x-16=6x+3 | | 50x+25y=100 | | 10=2(u+1) | | 50x+25x=100 | | 5x-7+2x=3x-3+4x-5+x |

Equations solver categories